Havy Tirosh-Samuelson krytyka transhumanizmu (Przegląd Religioznawczy – The Religious Studies Review, 2020)
The growing popularity of the ideas of transhumanists prompts philosophical reflection on this current of contemporary thought. Hava Tirosh-Samuelson in numerous publications analyzed the historical context of transhumanism and the significance of its most important theses. She undertook research on issues such as human nature, life extention, cyber-immortality, happiness, and religious aspects. Her fundamentally critical opinion about transhumanism is supported by sound arguments. The presented analyzes are certainly not final – they can inspire and encourage further research.